PENGARUH MODEL PEMBELAJARAN QUANTUM LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DITINJAU DARI SELF EFFICACY DI SMPN 1 KERITANG - Ayu Annisa, Tiara; Irma, Ade; Fitri, Irma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine whether there is an interaction effect between the quantum learning model and self efficacy on students’ mathematical problem solving abilities at SMP Negeri 1 Keritang. This research is motivated by the still low ability to solve mathematical problems, among which students do not yet understand the problem presented, due to students’ habit of working on exercises. The type of this research is an experimental study with a factorial experiment design. The population in the study consists of all seventh-grade classes, with classes VII.2 and VII.3 being the samples selected using the cluster random sampling technique. The instruments used are mathematical problem-solving ability test questions, a self-efficacy questionnaire, and observation sheets for teacher and student activities. The data analysis techniques used include normality tests, homogeneity tests, and two-way anova tests. Based on the analysis conducted, FAB = 5.761 > Ftabel = 3.156 was obtained. Because Fhitung is greater, Ha is accepted. In conclusion, there is an interaction effect between the applied quantum learning model and self-efficacy on mathematical problem-solving ability.